Transformer type superconducting fault current limiter with shunt impedance / Mohd Sobri Mohd Kamilan - Mohd Kamilan, Mohd Sobri (2009)
This proposal presents the transformer type superconducting fault current limiter (SFCL) to reduce the fault current in power transmission lines. Shunt impedance are being introduced in order to adjust the fault current and satisfy the required condition as a protective device.